TransgenicoAPP: A didactic application to help in classes on the topic of Transgenics (Research, Society and Development, 2022)
The use of mobile technologies as a tool to disseminate important issues to be discussed in society has been encouraged as an alternative to make the teaching and learning process more dynamic, accessible and modern. Considering this reality, this study aimed to develop a prototype of an application called “TransgenicoAPP” as a support tool for teachers to help teach the topic of Transgenics. The application has the advantage of being used offline, an indispensable factor due to the instability of the internet in the Amazon region. The application has the advantage of being used offline, an indispensable factor due to the instability of the internet in the Amazon region. Its layout, simplistic and intuitive, has eight tabs, containing the concept of transgenics; how they are produced; its applicability in the day-to-day; how to identify them; its advantages and disadvantages; its myths and truths; trivia to find out more and complementary videos. The developed application was disclosed to teachers of basic education 2, from schools in the city of Marabá-PA, with the intention of being evaluated by these professionals. The analysis of the assessments carried out by the professors showed great acceptance by them, due to the ease of use, richness of content and integrated technical knowledge. They considered it to be an excellent aid in teaching this topic and highlighted the possibility of using the application in their future classes.